Exploring the field of cultural production: The development of Pentigraf in Indonesia - Harendika, Melania Shinta; Salam, Aprinus; Sudibyo, Sudibyo (citeus, 2025)
This research examines the development of Pentigraf, an Indonesian minifiction form with a three-paragraph structure initiated by Tengsoe Tjahjono to suit modern, fast-paced culture. The emergence of Pentigraf and its community, i.e., KPI (Kampung Pentigraf Indonesian or the Indonesian Pentigraf Village), influenced the dynamics of the Indonesian field of cultural production. Using Bourdieu’s theory, it analyses Pentigraf’s position in cultural production from 2016-2023 based on literature reviews, media content analysis, competition records, and participatory observations in KPI. By studying the legitimacy and consecration of Pentigraf in the cultural production field, the research provides insights into how this literary format has been embraced by various institutions, serving as a medium for amateur writers. This research shows that Pen-tigraf has gained institutional support within the cultural production and has adapted to the literary environment by integrating conventional and digital to promote a new literary work. The position of Pentigraf moves from the left to the right below in Bourdieu’s diagram of cultural production, indicating its movement toward popular literature. The conclusion underscores the usefulness of Bourdieu’s framework in understanding new literary phenomena and highlights the implications of Pentigraf for the growth of popular literature in Indonesia.